Kesalahan Berbahasa Dalam Lagu “Tegar” Rossa: Dampaknya Terhadap Makna Dan Penyampaian Pesan - Ulfa Fatimah; Nabila Amanda Pulungan; Erbina Br Sembiring (BADAN PENERBIT STIEPARI PRESS, 2024)
Songs are an integral part of human life and play an important role in conveying messages and emotions. However, there are often language errors in song lyrics that go unnoticed. This article discusses language errors in the song